2021
DOI: 10.21154/cendekia.v1i1.2337
|View full text |Cite
|
Sign up to set email alerts
|

Education As an Attempt to Ward Off Islamophobia Virus in Strengthening Nationalism and Indonesian Spirituality

Abstract: The proliferation of Islamophobia worldwide, including Indonesia, can cause the erosion of the friendly image of Islam in the world. It needs an effort to ward off Islamophobia viruses in creating the peace and integrity of a nation. This article aims to present a variety of educational efforts to ward off Islamophobia viruses to strengthen the nationalism and spiritualization of the Indonesian. The study employed a qualitative approach through descriptive analysis methods. The results showed that one of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…31 According to Parhan et al, the presence of Aswaja Ke-NU is compatible with the concept of Islamic washatiyah in various countries. 32 Teachers in Madrasah Ibtidaiyah instil the nature of patriotismin lower class students (1,2, and 3) through subjects such as drawing and colouring, one of the basic elements that need to be instilled in students, 33 such as recognising the faces of heroes who fell on the battlefield, many cultures and customs in Indonesia, 34 such as traditional dances, musical instruments, costumes, and so on.…”
Section: Strengthening Patriotism In Madrasah Ibtidaiyahmentioning
confidence: 99%
“…31 According to Parhan et al, the presence of Aswaja Ke-NU is compatible with the concept of Islamic washatiyah in various countries. 32 Teachers in Madrasah Ibtidaiyah instil the nature of patriotismin lower class students (1,2, and 3) through subjects such as drawing and colouring, one of the basic elements that need to be instilled in students, 33 such as recognising the faces of heroes who fell on the battlefield, many cultures and customs in Indonesia, 34 such as traditional dances, musical instruments, costumes, and so on.…”
Section: Strengthening Patriotism In Madrasah Ibtidaiyahmentioning
confidence: 99%
“…In several previous studies, it was found that people should judge Islam with the best assessment, not even make Islam a scapegoat for bad events that befell them (Parhan, Budiyanti, et al 2021). Islam always renews the spirit of culture and the spirit of society in a much better life every day, such as straightening the culture of sacrificing the people of the archipelago who offer all of them to the gods and the spirits of their ancestors by changing the goal to express gratitude to Allah SWT for all the blessings that have been given.…”
Section: Religio Educationmentioning
confidence: 99%